Pragmatic competence and interpreter-mediated police investigative interviews. (3rd April 2017) - Gallai, Fabrizio
ABSTRACT: This article investigates discourse markers in interpreter-mediated police investigative interviews. Drawing on Goffman's participation framework and Sperber and Wilson's Relevance Theory, I show how pragmatic alterations of discourse markers in interpreters' renditions impact on contemporary police interviewing techniques and procedures. The discussion draws on analysis of authentic interpreter-mediated interviews and sheds light on the ways in which interpreting can disempower the interviewee as a result of substantive pragmatic interference. The article builds on earlier discussions about the interpreter's purported invisibility in legal interpreting and considers the role played by discourse markers in creating the illusion of an invisible mediator. I conclude that effectiveness of interrogation is affected by the extent to which interpreters and officers understand interpreters' pragmatic competence and call for greater attention to its development in police and interpreter training, and recognition in Codes of Practice.